Hubungan Kecerdasan Emosional dengan Hasil Belajar Biologi Siswa Kelas XI IPA SMA Negeri 1 Tanete Rilau Kabupaten Barru - Kurniawan, Muh Rizal; Hamka L, Hamka L; Hartati, Hartati (Universitas Negeri Makassar, 2018)
Abstract. Â This research is a correlational research that aims to determine the relationship of emotional intelligence with student biology learning outcomes. This research was conducted at SMA Negeri 1 Tanete Rilau of Barru District. Population in this research was class XI IPA SMA Negeri 1 Tanete Rilau, with total of sample are 60 students selected by random sampling technique that was random sample determination. The research instrument in question is a questionnaire of students' emotional intelligence and learning outcomes on the material of the respiratory system, digestive system and excretion system. Data analysis technique used is descriptive analysis and inferential analysis using normality test, linearity test and correlation test using Product Moment Correlation. Based on the results of data analysis using SPSS obtained a significance value of 0.006 <Î± (0.05) indicated that there was a relationship between emotional intelligence and student learning outcomes. Based on the data analysis, it can be concluded that there was a relationship between emotional intelligence and biology learning outcomes student class XI IPA SMA Negeri 1 Tanete Rilau Barru District. Keywords:Â emotional intelligence, learning outcames, relationship